2020
DOI: 10.1111/ejed.12418
|View full text |Cite|
|
Sign up to set email alerts
|

Language teacher multilingualism in Norway and Russia: Identity and beliefs

Abstract: Multilingualism has witnessed growing interest as a subject of academic study and as a state to aspire to for many of the world's citizenry. In tandem with this growing interest, countries around the world have started to implement foreign language curricula at schools that seek to prepare the coming generations to thrive in an increasingly multilingual global environment. In this respect, language teachers are likely to play a pivotal role in promoting the learning of multiple languages among students, with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 43 publications
(72 reference statements)
1
15
0
1
Order By: Relevance
“…Several participants talked about their multilingual students generally performing better in class, possessing heightened cognition, and drawing on crosslinguistic comparisons. The participants’ beliefs about the benefits of being multilingual when learning a language support the findings from other studies where teacher participants reported similarly positive beliefs about multilingualism (e.g., Calafato, 2020b). However, their positive beliefs did not always lead them to draw on their students’ multilingualism during lessons: approximately half of the participants did not draw on their students’ knowledge of other languages when teaching Arabic.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Several participants talked about their multilingual students generally performing better in class, possessing heightened cognition, and drawing on crosslinguistic comparisons. The participants’ beliefs about the benefits of being multilingual when learning a language support the findings from other studies where teacher participants reported similarly positive beliefs about multilingualism (e.g., Calafato, 2020b). However, their positive beliefs did not always lead them to draw on their students’ multilingualism during lessons: approximately half of the participants did not draw on their students’ knowledge of other languages when teaching Arabic.…”
Section: Discussionsupporting
confidence: 83%
“…This can make it difficult to determine how widespread such practices are in any given context. Therefore, it would be informative if a comparative approach was employed to analyze teacher beliefs and practices among larger populations based on their level of multilingualism (e.g., Calafato, 2020b). This would help us see whether there are overarching trends regarding how teachers report benefitting from their knowledge of other languages and if being multilingual correlates positively with their reported implementation of crosslinguistic practices in the classroom.…”
Section: Self‐regulation the Multilingual Teacher And Arabicmentioning
confidence: 99%
“…First, there is a need for more contrastive analysis within and between countries (e.g., De Angelis, 2011) when it comes to researching FL teachers' implementation of MTPs so that we may obtain a better understanding of how macro-level factors like language policy, language ideologies, and nationality affect this implementation (Douglas Fir Group, 2016;Gee, 2001). Secondly, research on FL teacher multilingualism and the implementation of MTPs is mostly non-existent in the Russian context (Calafato, 2020b(Calafato, , 2021b and remains understudied in the Norwegian one (exceptions to this include Haukås, 2019;Lorenz et al, 2021). Norway and Russia also make for an interesting comparison in that they are neighbors, yet the former is firmly situated in Europe, geographically and culturally, while the latter has a more hybrid identity (Davydova, 2019;Protassova, 2010).…”
Section: Foreign Language Education In Norway and Russiamentioning
confidence: 99%
“…Teachers' tendency to refer to languages they know themselves suggests a teacher-centred approach to multilingualism wherein teachers are the experts who provide explicit contrastive grammatical explanations instead of giving learners tools to become increasingly independent explorers of languages and their own multilingual identity. An interesting study of language teachers' beliefs about and approaches to multilingualism in Norwegian and Russian schools showed that highly multilingual teachers had a stronger resource orientation towards multilingualism than teachers with fewer languages in their linguistic repertoire (Calafato, 2020). Furthermore, teachers who taught more than one language subject reported using a multilingual pedagogy more often than those teaching only one language subject.…”
Section: Teachers' Beliefs About and Approaches To Multilingualismmentioning
confidence: 99%